Jack the giant slayer [videorecording (DVD)] - Singer, Bryan, 1965-; Hoult, Nicholas, 1989-; Tomlinson, Eleanor, 1992-; Tucci, Stanley; McShane, Ian, 1942-; Nighy, Bill, 1949-; McGregor, Ewan, 1971- (Warner Home Video, 2013)
Jack the Giant Slayer tells the story of an ancient war that is reignited when a young farmhand unwittingly opens a gateway between our world and a fearsome race of giants. Unleashed on the Earth, the giants strive to reclaim the land they once lost, forcing Jack into the battle of his life to stop them. Fighting for a kingdom, its people, and the love of a brave princess, he comes face to face with the unstoppable warriors he thought only existed in legend, and gets a chance to become a legend.